Microwave – assisted hydrothermal synthesis of nanocrystal β-Ni(OH)2 for supercapacitor applications. Issue 18 (19th April 2016) - Elshahawy, Abdelnaby M.; Ho, Kuan Hung; Hu, Yating; Fan, Zhen; Hsu, You Wei Benedict; Guan, Cao; Ke, Qingqing; Wang, John
Abstract : Nanocrystalline β-Ni(OH)2 was successfully synthesized by a microwave assisted hydrothermal process. Abstract : Nanocrystalline β-Ni(OH)2 was successfully synthesized by a microwave assisted hydrothermal process. The effects of different surfactants/additives, such as cetyltrimethylammoniumbromide (CTAB) as a cationic surfactant, sodium dodecyl sulfate (SDS) as an anionic surfactant and ethylendiamine (EDA) and polyvinylpyrrolidone (PVP), on the resultant structure, morphology, specific surface area and electrochemical performance, were investigated. The crystallinity of β-Ni(OH)2 was shown to play a dominate role in the electrochemical performance. The nanocrystalline β-Ni(OH)2 derived from CTAB showed a ∼1566 F g −1 high specific capacitance at 1 A g −1 in 6 M KOH (1958 F g −1 based on the mass of β-Ni(OH)2 ) and 91% retention after 1000 charge–discharge cycles at 10 A g −1 . The excellent electrochemical performance is attributed to the well-defined nanocrystallinity of the hexagonal β-Ni(OH)2 nanoplates.